The Religion of Consumer Capitalism and the Construction of Corporate Sacred Spaces - Coudert, Allison P. (Religions, 2023)
If one looks at the United States over the past sixty years, it becomes clear that religious and spiritual practices have proliferated in unexpected places and spaces. They have become thoroughly ensconced in the boardrooms, offices, shop floors, and retail spaces of business establishments. From there, they have seeped into just about every imaginable area of American life, turning schools, parks, shopping malls, sports stadiums, hospitals, gyms, health food restaurants, spas, and the very apps on our computers and cell phones into corporate spaces promising new and enticing forms of spiritual enchantment. The purpose of this essay is to document the way new forms of spirituality have become part of a much longer history of the entanglement of business and religion, a history that began in monasteries, formed the bedrock of the Puritan work ethic, and is now an established aspect of the neoliberal ideal of the privatization and corporatization of all aspects of human life.